RETRACTED: PENGARUH METODE PEMBELAJARAN DISCOVERY MENGGUNAKAN E-LEARNING TERHADAP KEMAMPUAN LITERASI MATEMATIS SISWA - Hendry Sugianto; Amin Suyitno; Tri Sri Noor Asih (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2022)
Following a rigorous, carefully concerns and considered review of the article published in Jurnal Edukasi dan Sains Matematika (JES-MAT) to article entitled “PENGARUH METODE PEMBELAJARAN DISCOVERY MENGGUNAKAN E-LEARNING TERHADAP KEMAMPUAN LITERASI MATEMATIS SISWA” Vol 8, No 1, pp. 95-106, March 2022, DOI: https://doi.org/10.25134/jes-mat.v8i1.5594This paper has been found to be in violation of the Jurnal Edukasi dan Sains Matematika (JES-MAT) Publication principles and has been retracted.The article contained redundant material, the editor investigated and found that the paper published in JNPM (Jurnal Nasional Pendidikan Matematika), Vol. 6, No. 1, pp. 145-157, 2022, DOI : 10.33603/jnpm.v6i1.6264, URL: https://jurnal.ugj.ac.id/index.php/JNPM/article/view/6264 entitled "PENGARUH METODE PEMBELAJARAN DISCOVERY MENGGUNAKAN E-LEARNING TERHADAP KEMAMPUAN LITERASI MATEMATIS MTS ".The document and its content has been removed from Jurnal Edukasi dan Sains Matematika (JES-MAT), and reasonable effort should be made to remove all references to this article.